Purine metabolism in adenosine deaminase deficiency. - Mills, G C (1976)
Purine and pyrimidine metabolites were measured in erythrocytes, plasma, and urine of a 5-month-old infant with adenosine deaminase (adenosine aminohydrolase, EC 3.5.4.4) deficiency. Adenosine and adenine were measured using newly devised ion exchange separation techniques and a sensitive fluorescence assay. Plasma adenosine levels were increased, whereas adenosine was normal in erythrocytes and not detectable in urine. Increased amounts of adenine were found in erythrocytes and urine as well as in the plasma. Erythrocyte adenosine 5'-monophosphate and adenosine diphosphate concentrations were normal, but adenosine triphosphate content was greatly elevated. Because of the possibility of pyrimidine starvation, pyrimidine nucleotides (pyrimidine coenzymes) in erythrocytes and orotic acid in urine were measured. Pyrimidine nucleotide concentrations were normal, while orotic acid was not detected. These studies suggest that the immune deficiency associated with adenosine deaminase deficiency may be related to increased amounts of adenine, adenosine, or adenine nucleotides.